G591(P) Are we losing the battle against infections? An audit on antimicrobial resistance. (25th October 2020) - Rehman, L; Kamal, M; Neenan, F; Hussain, M; Shahid, M
Abstract : Aim: To analyse the practice of prescribing outpatient antibiotics and check adherence to antimicrobial guidelines in the Paediatric Emergency Department (PED) of a university hospital. Method: All children, prescribed antibiotics before discharge from PED were included. Pre-intervention, 55 charts in between Feb-April 2019 were audited retrospectively for prescribing 1)Correctly indicated antibiotics against certain infections based on clinical judgement and/or investigations, 2)Correct choice, 3)Duration and 4)Dose against standards as mentioned below in references. 1 2 3 4 5 6 7 Post-intervention, 30 charts were audited between May-July 2019 to re-check adherence to recommended standards. Standards were redefined and implemented for common infections encountered in PED by physicians as per results of the audit. Clinical judgment was deemed optimal if it followed the standard. 1 2 3 4 5 6 7 Results: Pre interventions, only 56% of antibiotics were correctly indicated for certain infections. Post intervention, 96% were correctly indicated, resulting in an improvement of 20%. Regarding prescribing the correct type of antimicrobials, antibiotic guidelines were adhered to 84% of the time. This rose to 100% post-intervention. Of the antibiotics prescribed, 41% of outpatients were prescribed an insufficient dose which declined to 3% after intervention. Conclusion: Despite, substantially reduced mortality from infectious diseases by advances in antimicrobials, resistance is growing at an alarming rate. This rise in antimicrobial resistance is one of the greatest potential threats to human health at global levels with serious consequences for public health, animal health and welfare. 8 9 Outpatient antimicrobial scripts are being written in the PED on a daily basis by junior doctors who rotate from different specialities every six months. Also, factors such as sub-optimal clinical judgement, parental reassurance and heavy workload in PED might contribute to excessive prescription. Our audit prompted us to make standards clear for all NCHDS. Our interventions reduced the margin of error substantially. References: Childhood Pneumonia, Faculty of Paediatrics (RCPI), HSE Guidelines, Feb 2014 Urinary Tract Infection, Faculty of Paediatrics (RCPI), HSE Guidelines Acute Otitis Media, Faculty of Paediatrics (RCPI), HSE Guidelines Sore throat (acute): antimicrobial prescribing, National Institute for Health and Care Excellence(NICE) guidelines, 2018 Our Lady's Children Hospital Formulary, OLCHC/TSCUH ANTIBIOTIC GUIDELINES Galway Antimicrobial Prescribing Principles(GAPP) BNF For Children 2019 https://health.gov.ie/blog/publications/irelands-national-action-plan-on-antimicrobial-resistance-2017–2020/ https://www.who.int/antimicrobial-resistance/global-action-plan/en/